Hybrid Filler Actions on Functional Performance Evaluation of Magnesium Alloy (AZ61) Hybrid Nanocomposites - Venkatesh R.; Logesh K.; Singh P.K.; Vinayagam M.; Hossain I.; Soudagar M.E.M.; Al Obaid S.; Alharbi S.A.; Ramachandaramurthy V.K. (Springer Science and Business Media Deutschland GmbH, 2025)
The proposed research of magnesium alloy (AZ61) hybrid nanocomposites followed by advanced liquid-state processing associated with the squeeze die-cast process overcomes the drawbacks (micro-voids, agglomerated particles, and oxidation during open melting) of conventional liquid stir gravity die casting. The boron nitride (BN) and silicon carbide (SiC) nanoparticles are the source of hybrid filler material for composing the AZ61 alloy hybrid nanocomposites. Finding the role of hybrid filler materials during the squeeze casting processing on surface morphological, mechanical, and tribological performance is evaluated by the ASTM standard, and its outcomesare comparedwith cast AZ61 alloy and AZ61/3 wt% of BN nanocomposites. The advanced liquid-state processing features with squeeze die cast proved void-free structure composite surface and homogenous particle distribution was confirmed by scanning electron microscope analysis. The crystal peaksare confirmedwith the support of X-ray diffraction analysis. Besides, the actions of hybrid filler material in AZ61 alloy matrix provided significant results and the composite contained with 3 wt% of BN 7.5 wt% SiC offered improved density (1.851g/cc), reduced porosity (0.54%), optimum yield, and ultimate tensile strength performance of 184.7 9 and 307.1 6MPa, maximum hardness (84.6 4HV), hiked impact strength (24.2 1J/mm2), reduced volumetric wear loss (0.97mm3/m) and improved coefficient of friction (0.47). The best functional performance of composite sample (AZ61/3 wt% BN/7.5 wt% SiC)is advisedfor automotive top roof frame applications. ? American Foundry Society 2024.